IDEAS: A tool for improved evaluation and utilization of animal genetic resources - Wissocq, N.M.; Bell, R.J.; Durkin, J.W.; Gettinby, George; Light, D. (ILCA/ILRAD, 1988)
Discusses the potential of IDEAS - ILCA's Data entry and Analysis system, key for success including accuracy, rapidity & simplicity, and examines the impact of IDEAS in Africa.